Structural, Electronic, Elastic, and Optical Properties of Cubic BaLiX3 (X = F, Cl, Br, or I) Perovskites: An Ab-initio DFT Study - Redi Kristian Pingak; Soukaina Bouhmaidi; Larbi Setti; Bartholomeus Pasangka; Bernandus Bernandus; Hadi Imam Sutaji; Fidelis Nitti; Meksianis Zadrak Ndii (Indonesian Journal of Chemistry, 2023)
This study reports for the first time the theoretical prediction of structural, electronic, elastic and optical properties of cubic BaLiCl3, BaLiBr3, and BaLiI3 perovskites. The corresponding properties of the well-known BaLiF3 are also theoretically investigated. Density Functional Theory (DFT) using the Generalized Gradient Approximation (GGA) was implemented within the Quantum Espresso package to investigate the properties of the perovskites. The results revealed that BaLiX3 (X = F, Cl, Br, and I) are in ionic crystal forms with optimized lattice parameters of 4.04, 4.90, 5.21, and 5.66 Å, respectively. The minor band gaps were found to be 6.62 eV (Γ→Γ), 4.29 eV (R→Γ), 3.50 eV (R→Γ), and 2.58 eV (R→Γ) for the respective compounds. The investigation of their elastic properties indicated that these perovskites are all mechanically stable, while only BaLiBr3 and BaLiI3 are malleable. Finally, the studied perovskites exhibit excellent optical properties, including low reflectivity and high absorption in the ultraviolet region. Hence, it is predicted that these perovskites are suitable for various optoelectronic applications involving absorption in the UV region. However, BaLiBr3 and BaLiI3 are more favorable than BaLiF3 and BaLiCl3 to be deposited as thin films due to their flexibility.